The Role of Government in the Issue of Legalizing Marijuana for Medical Purposes in Indonesia (in Press) - Yanti Mingka, Putri Manja; Larasati, Endang; Lituhayu, Dyah (Publik : (Jurnal Ilmu Administrasi), 2024)
Cannabis is a plant that has medicinal benefits. However, the use of cannabis is prohibited by Indonesian Law Number 35 of 2009 concerning Narcotics. Cannabis has a million benefits that can be used in medicine. The government must take this effect into account because legalizing cannabis for medical use has many benefits from various perspectives. And this will have an impact on the economy, industry, and a number of other sectors. However, the government's attitude towards the benefits of cannabis for medical use has not responded well, the Indonesian government is still silent without any explanation to the public regarding this issue. This research uses a normative juridical approach with conceptual and case law methods. Cannabis is classified as a Group I narcotic, prohibiting its medical use under current regulations, allowing only scientific research and diagnostic purposes. Despite its potential as a treatment, cannabis has not been approved by the National Narcotics Agency (BNN) or the government for medicinal use. Article 41 of the Narcotics Law suggests revising the classification of cannabis to allow its use for medical treatments or palliative care under strict supervision. A specialized government agency could oversee its distribution, ensuring it is used safely and according to medical prescriptions